Analysis of fluoride pollution from fertilizer industry and phosphogypsum piles in agricultural area - (:unkn) unknown (Research and Reviews, 2017)
Soil fluoride pollution due to small and large scale industrial plants and phosphogypsum (PG) as a by-product of a chemical fertilizer production plant (CFPP) in Bandırma district in Turkey was studied. The soil fluoride concentrations of the samples varied in the range of 75 mg/kg to 884 mg/kg with an average of 300 mg/kg ± 195 mg/kg. The average fluoride amount in the soils around the world has been exceeded in many areas in prevailing wind directions, varying in 394 mg/kg ± 884 mg/kg, while it was lower (30 mg/kg to 380 mg/kg) in other directions. Spatial soil fluoride map showed that the fluoride has been transported up to 15 km away by atmospheric transportation under the influence of prevailing winds. High fluoride concentrations measured in PG samples varied in the range of 2320 mg/kg to 3400 mg/ kg. We conclude that atmospheric transportation of PG and fluoride containing emissions of CFPP may be the cause of fluoride accumulation and the pollution in the soils located around.
Keywords: Chemical fertilizer industry; Fluoride; Phosphogypsum; Soil pollution; Spatial distribution